2012
DOI: 10.3126/kumj.v10i1.6918
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Relationships of Scores Obtained in Grades 10 and 12 with the Entry and Success in Undergraduate Medical Education

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…23 Similar observation was reported from Gautam et al in a study of Medical students at Nepal. 1 The present study found no relationship between the performance of students in medical college vis a vis their language of instruction during schooling. This implies that the students from any vernacular medium cope reasonably to instructions in English and that it does not affect their performance.…”
Section: Language Barriercontrasting
confidence: 80%
See 1 more Smart Citation
“…23 Similar observation was reported from Gautam et al in a study of Medical students at Nepal. 1 The present study found no relationship between the performance of students in medical college vis a vis their language of instruction during schooling. This implies that the students from any vernacular medium cope reasonably to instructions in English and that it does not affect their performance.…”
Section: Language Barriercontrasting
confidence: 80%
“…The most important being, what criterion if applied, can select the best candidates as future doctors. 1 Many studies across the world have tried to explore various cognitive and non-cognitive predictors which entrance test) for admissions to medical colleges.…”
Section: Introductionmentioning
confidence: 99%